2021
DOI: 10.1002/ldr.4050
|View full text |Cite
|
Sign up to set email alerts
|

Assessing salt marsh loss and degradation by combining long‐term LANDSAT imagery and numerical modelling

Abstract: The precise evaluation of the conservation status of salt marshes, the understanding of the mechanisms behind loss and degradation and the anticipation of future threats are fundamental to assist management solutions able to reverse the declining trend observed in these environments. Previous methods combining remote sensing and hydrodynamic modelling have been revealed to be effective in assessing degradation in restricted marshes, but unable to characterise dynamics of marshes at the estuarine scale. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…However, a recent study [16] concluded that the lagoon deepened since 1987, because of dredging activities performed in the late 1990s and due to the ebb dominance of the inlet and central lagoon area, that promotes sediments exportation from these areas to the adjacent ocean. In turn, [19] verified that the salt marshes of the lagoon have been degraded mainly after the lagoon deepening. These findings suggest that future inundation extents can be even higher than those projected in this study if this evolutionary trend continues in the future.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…However, a recent study [16] concluded that the lagoon deepened since 1987, because of dredging activities performed in the late 1990s and due to the ebb dominance of the inlet and central lagoon area, that promotes sediments exportation from these areas to the adjacent ocean. In turn, [19] verified that the salt marshes of the lagoon have been degraded mainly after the lagoon deepening. These findings suggest that future inundation extents can be even higher than those projected in this study if this evolutionary trend continues in the future.…”
Section: Discussionmentioning
confidence: 73%
“…On the one hand, when these regions change to subtidal, these habitats tend to disappear, making it impossible for several species to survive in the new conditions, as showed by [40]. On the other hand, the general increase in the MSSE on the intertidal areas and salt marshes can indirectly affect the local vegetation, since their roots will possibly be flooded during longer periods and consequently less oxygenated, which, according to previous studies [19,40], may have adverse consequences on the salt marsh extent and, therefore, on the local ecosystems.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Remote sensing retrieval of SMC outperforms traditional measurement methods because it provides the electromagnetic spectrum reflected from the soil surface quickly and over a long time. Moreover, remote sensing methods are characterized by their wide monitoring range, high processing speed, and low cost (Lopes et al, 2021; Tripathi & Tiwari, 2021). There are several remote sensing methods, such as reflectance and vegetation index methods based on visible near‐infrared (Przeździecki & Zawadzki, 2020; Tian et al, 2021; Zhou et al, 2022), thermal inertia method based on thermal infrared (Gao et al, 2022; Nguyen et al, 2022), temperature dryness vegetation index method (Wei et al, 2020; Xu et al, 2022), and soil moisture retrieval based on active and passive microwaves (Rigden et al, 2020; Song et al, 2021; Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%